Extreme cervical elongation - PB, Hiremath; Bansal, Nidhi; Hiremath, Reshma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Uterine prolapse is a condition which has commonly affected women of all times. The problem of genital prolapse and its remedies is described in the oldest medical literature, the Egyptian Papyri. The normal length of the cervix is about 2.5 cm. The vaginal and supravaginal parts are of equal length. The elongation may affect either part of the cervix. The length of the uterocervical canal is measured by introduction of the uterine sound. Cervical elongation plays an important role in deciding the surgical treatment. We had a case of extreme cervical elongation and we faced difficulties during the surgery.